Re-exploration of U’s Triangle Brassica Species Based on Chloroplast Genomes and 45S nrDNA Sequences - Chang-Kug Kim (Nature Portfolio, 2018)
Abstract The concept of U’s triangle, which revealed the importance of polyploidization in plant genome evolution, described natural allopolyploidization events in Brassica using three diploids [B. rapa (A genome), B. nigra (B), and B. oleracea (C)] and derived allotetraploids [B. juncea (AB genome), B. napus (AC), and B. carinata (BC)]. However, comprehensive understanding of Brassica genome evolution has not been fully achieved. Here, we performed low-coverage (2–6×) whole-genome sequencing of 28 accessions of Brassica as well as of Raphanus sativus [R genome] to explore the evolution of six Brassica species based on chloroplast genome and ribosomal DNA variations. Our phylogenomic analyses led to two main conclusions. (1) Intra-species-level chloroplast genome variations are low in the three allotetraploids (2~7 SNPs), but rich and variable in each diploid species (7~193 SNPs). (2) Three allotetraploids maintain two 45SnrDNA types derived from both ancestral species with maternal dominance. Furthermore, this study sheds light on the maternal origin of the AC chloroplast genome. Overall, this study clarifies the genetic relationships of U’s triangle species based on a comprehensive genomics approach and provides important genomic resources for correlative and evolutionary studies.